Detection of ultrasonic plate waves using ceramic strip transducers - Claes, Leander; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (Proceedings SENSOR 2015)
Keywords: piezoceramics; strip transducers; plate waveguide; dispersion diagram

Piezoelectric applications of hydrothermal lead-free (K0.48Na0.52)NbO3 ceramics - Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics Symposium (IUS), 2012 IEEE International)
A hydrothermal method utilizes a crystallization process in the solution so that the pure and high-quality powders can be realized. Sintering from the hydrothermal KNbO3 and NaNbO3 powders, a high-dense lead-free piezoelectric (K,Na)NbO3 ceramics could be obtained (density: 98.8%). Concerning about the g33 constant, high value as large as commercial PZT ceramics was measured. Therefore, the hydrothermal (K,Na)NbO3 ceramics is usable for the sensors and the energy harvesting devices. To demonstrate the (K,Na)NbO3 ceramics, a hydrophone sensor was fabricated and evaluated.
Keywords: crystallisation; hydrophones; piezoceramics; potassium compounds; powder technology; powders; sensors; sintering; sodium compounds; (K0.48Na0.52)NbO3; KNbO3 powder; NaNbO3 powder; crystallization; energy harvesting devices; g33 constant; hydrophone sensor; hydrothermal lead-free (K0.48Na0.52)NbO3 ceramics; hydrothermal method; piezoelectric applications; sintering; Materials; Transducers

Multi-DOF cylindrical piezoelectric actuator with radial polarization - Lucinskis, Raimundas; Mazeika, Dalius; Hemsel, Tobias; Bansevicius, Ramutis (AIP Conference Proceedings)
The paper presents the results of numerical and experimental investigation of cylindrical piezoelectric actuator used for achieving independent three degrees of freedom oscillations of the contact point. The design of actuator based on a hollow piezoelectric cylinder mounted on a metal rod. The piezoceramic cylinder has a radial polarization and special configuration of the electrodes that cover inner and outer surface of the cylinder. The main advantage of actuator's design is that solid metallic rod operates as a part of inner electrode of the cylinder and a stator of actuator. The geometry of piezoelectric actuator was adopted to reach resonance of oscillations for the first longitudinal mode and the third flexural mode at same frequency. The actuator is designed to move positioned object through contact point which is located on the top of the rod. The optimal topology of electrodes was found to achieve longitudinal and flexural oscillations of the actuator in two perpendicular planes. Three degrees of freedom of the positioning object can be achieved and control of the system can be implemented by applying different excitation schemes and regimes. The numerical simulation and experimental study of piezoelectric actuator was performed. Impedance of actuator was analyzed under different excitation regimes. The results of numerical modeling and experimental study were compared. Recommendations for the further development of this type of actuator are given.
Keywords: dielectric polarisation; piezoceramics; piezoelectric actuators